Engaging Schooling Subjectivities Across Post-apartheid Urban Spaces - Fataar, Aslam (African Sun Media, 2015)
Aslam Fataar, one of South Africa's few educational sociologists working with ethnographic methods, captures the complex interactions and dynamics between social life, school processes and youth subjectivity in townships in the Western Cape. His work with concepts of mobilities and space is enormously generative, providing a way for teachers, principals, communities and policy makers to engage with the 'complex ecologies' of young people's learning in urban schools. As an astute policy analyst, he also well knows the systemic barriers in the way of achieving this. The last chapter, on possibilities for pedagogical justice at the site of the school, considers how disengaged students might re-engage through leveraging explicit pedagogic connections between their lifeworlds and school practices. Acknowledging that pedagogy cannot be the only means for revitalising schooling, the author nevertheless insists that marginalised young people's consent needs to be won by schools that make use of, rather than ignore, their strengths, knowledges and aspirations. The approach to the troubled question of youth and subjectivity is enlightening, and vital to understanding the post-apartheid city and school. The book fills a much-needed gap in educational sociology in South Africa.